Maritime lexis in the Russian-Polish dictionary by Piotr Dubrowski as a starting point for chronology-oriented studies of Polish maritime terms - Mędelska, Jolanta; Wierzchoń, Piotr (Papers in Linguistics, 2023)
The authors discussed the development of maritime lexis in Russian and Polish, pointing out a great preponderance of Russian over Polish instances which lasted until the interwar period. They analysed 70 entries with the qualifier w Marynarce [maritime] (letters K–L) in a 19th-century Russian-Polish dictionary. They found that the editor had managed to select Polish equivalents for only 22 Russian terms (31%), with the remainder provided only with descriptions of meaning. Using sources available today, the authors identified 74 translations for 48 Russian units left untranslated and subjected them to chronological analysis. They found that 16 of them were in use in Dubrowski’s times, seven of which for a very long time prior to the date of publication of his dictionary. The others appeared only after the dictionary was published, the majority (42) as late as 1920–1939, with seven more appearing even later.